2021
DOI: 10.1039/d1tc00791b
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of blue-emitting bromide-based perovskite nanoplatelets towards unity quantum efficiency and ultrahigh stability

Abstract: All-inorganic cesium lead halide perovskite nanocrystals have been widely investigated as promising materials for light and display. The primary challenge for their practical application is development of highly efficient and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Lead halide perovskites with the APbX 3 (X = Cl, Br, I) structure with organic (e.g., methylammonium (MA + ) or formamidinium (FA + )) or inorganic (Cs + ) A-site cations have emerged as promising candidates for various optoelectronic applications ranging from photovoltaics , to X-ray and γ-detectors, light-emitting devices (LEDs), lasers, , and quantum light sources. , Most notably, colloidal perovskite quantum dots (QDs) have demonstrated outstanding suitability for display applications with near-unity photoluminescence quantum yields (PLQY), excellent long-term stability, and narrow emission at room temperature, as well as beneficial properties for quantum emitters with long exciton coherence times and ultrafast emission at cryogenic temperatures. , Size engineering of such structures recently allowed the formation of highly anisotropic CsPbBr 3 nanoplatelets (NPLs), introducing strong asymmetric quantum confinement and emission colors in the turquoise/blue spectral range, while maintaining high quantum yields and stability. …”
mentioning
confidence: 99%
“…Lead halide perovskites with the APbX 3 (X = Cl, Br, I) structure with organic (e.g., methylammonium (MA + ) or formamidinium (FA + )) or inorganic (Cs + ) A-site cations have emerged as promising candidates for various optoelectronic applications ranging from photovoltaics , to X-ray and γ-detectors, light-emitting devices (LEDs), lasers, , and quantum light sources. , Most notably, colloidal perovskite quantum dots (QDs) have demonstrated outstanding suitability for display applications with near-unity photoluminescence quantum yields (PLQY), excellent long-term stability, and narrow emission at room temperature, as well as beneficial properties for quantum emitters with long exciton coherence times and ultrafast emission at cryogenic temperatures. , Size engineering of such structures recently allowed the formation of highly anisotropic CsPbBr 3 nanoplatelets (NPLs), introducing strong asymmetric quantum confinement and emission colors in the turquoise/blue spectral range, while maintaining high quantum yields and stability. …”
mentioning
confidence: 99%
“…[15,29,53,119,121] These methods include in situ passivation during synthesis or post-synthetic passivation of surface vacancies (Figure 10a,c,d). [15,29,53,117,122,123] For instance, Bohn et al demonstrated a drastic improvement in the PL of CsPbBr 3 NPls by post-synthetic treatment with a solution consisting of metal halides complexed with OLA and OA ligands (Figure 10a,b). [29] After comparing several metal halides, they found that the maximum PL enhancement was obtained with PbBr 2 -ligand, suggesting that both the Pb and Br vacancies are responsible for the lower PLQY of CsPbBr 3 NPls.…”
Section: Surface Passivated Halide Perovskite Nanoplateletsmentioning
confidence: 99%
“…[ 15,29,53,119,121 ] These methods include in situ passivation during synthesis or post‐synthetic passivation of surface vacancies (Figure 10a,c,d). [ 15,29,53,117,122,123 ] For instance, Bohn et al. demonstrated a drastic improvement in the PL of CsPbBr 3 NPls by post‐synthetic treatment with a solution consisting of metal halides complexed with OLA and OA ligands (Figure 10a,b).…”
Section: Synthesis Of Nanoplateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the use of surface capping agents and the dimensionality of the perovskite structure also affects the PLQYs and stability even for the same CsPbX 3 compositions. 116,[119][120][121][122] Dutta et al 116 reported the near-unity PLQYs in CsPbX 3 (X = Cl, Br, I) NCs. To achieve near-unity PLQYs, the oleylammonium halide was used as a precursor.…”
Section: 42mentioning
confidence: 99%